The Importance of Conducting Need Analysis to Design English Courses in Curriculum Merdeka - Umi Maisarah; Rahmadi Nirwanto (PT. Padang Tekno Corp, 2024)
This article explains the importance of conducting a needs analysis in developing an English language course for an open curriculum. The independent curriculum is a learning framework that aims to holistically improve students' English language skills while considering local needs and contexts. In this context, needs analysis has become an important stage in ensuring that the material, techniques, and evaluation in the English language course meet the needs of students. The article discusses the importance of needs analysis in designing English language courses. Needs analysis helps determine appropriate learning objectives and guides curriculum development. The curriculum can be designed to integrate relevant and practical language skills while comprehensively assessing student needs. Additionally, needs analysis allows for the customization of learning programs to student characteristics. Each group of students has unique backgrounds, interests, and demands. By studying students' needs specifically, teachers can select and design resources that are appropriate for their skill level, interests, and context. This will encourage students to learn. The article also emphasizes the importance of involving students in the needs analysis process